2014
DOI: 10.3788/col201412.041403
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synthesis of Fe-Mn-Si-Cr-Ni shape memory alloy functional coating by laser cladding

Abstract: Fe-Mn-Si-Cr-Ni composite powders are utilized to form a functional shape memory alloy cladding layer (SMACL) using a laser cladding method. The microstructure, microhardness, and phase composition of the SMACL are measured, and the extent of deformation of the laser cladding samples is determined. The SMACL is composed of planar, cellular, and dendritic crystals, equiaxed grains, and oxides with increasing distance from the substrate surface. The SMACL is further composed of ε-martensite and γ-austenite phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…From this equation (1), it is seen that when the coating powders were melted, reaches a maximum value. Hence, drops down to a minimum value, which means high-entropy phases are stable under high temperature, and because of the cooling rate as high as 10 6 –10 7 °C s −1 during laser cladding, the elevated temperature structure cannot be decomposed, stayed to room temperature, which is complied with sluggish diffusion effect in HEAs [24].…”
Section: Resultsmentioning
confidence: 99%
“…From this equation (1), it is seen that when the coating powders were melted, reaches a maximum value. Hence, drops down to a minimum value, which means high-entropy phases are stable under high temperature, and because of the cooling rate as high as 10 6 –10 7 °C s −1 during laser cladding, the elevated temperature structure cannot be decomposed, stayed to room temperature, which is complied with sluggish diffusion effect in HEAs [24].…”
Section: Resultsmentioning
confidence: 99%
“…Further. Wide distortion and residual stress arise in stainless steel (AISI 304) after laser cladding has been noticed by P. Xu, H. Ju, C. Lin, C .Zhou, and D. Pan (22) when he has performed experiments by using Fe17Mn5Si10Cr5N. S. Zhao, S. Zhou, M. Xie, X Dai, D. Chen, and L.C Zhang, L. C (23) to investigate the effect of Cu88Fe12 immiscible coating on phase separation and improved wear resistance fabricated of Cu88Fe12 immiscible coating with Fe-12%, Ni-5%, Cr-0.6%, Si-0.2% on low carbon steel and found that Fe-rich coating show higher hardness than Cu rich coating.…”
Section: Ecs Transactions 107 (1) 5047-5057 (2022)mentioning
confidence: 88%
“…Ju [17] found that the characteristic of stress self-accommodation of Fe-Mn-Si shape memory alloy can effectively reduce the residual stress generated by laser welding and has excellent mechanical properties. Xu [18] successfully prepared a Fe-Mn-Si(SMA) coating on the surface of 304 stainless steel, which has the characteristic of stress self-accommodation. The residual stress generated during the solidification process induces γ → ε martensite transformation [19,20].…”
Section: Introductionmentioning
confidence: 99%